ALTERNATIVE ACCOMMODATION OF AN UNLAWFUL OCCUPIER’S CHOOSING: SOME REFLECTIONS ON Grobler v Phillips [2022] ZACC 32 - Lerato Rudolph Ngwenyama (Obiter, 2023)
An abundance of case law dealing with eviction has emerged. Clear rules for evictions exist in the eviction context and a solid body of law is being developed in this regard. For many years, little attention was given to the issue of unlawful occupiers refusing to be evicted based on preferences or wishes to remain in the same house or land under the Prevention of Illegal Eviction From and Unlawful Occupation of Land Act 19 of 1998 (PIE). However, in recent years disputes around the choice of alternative accommodation in terms of the Extension of Security of Tenure Act 62 of 1997 (ESTA) have increased significantly.